2018
DOI: 10.1371/journal.pone.0202667
|View full text |Cite
|
Sign up to set email alerts
|

The VP1 unique region of human parvovirus B19 and human bocavirus induce lung injury in naïve Balb/c mice

Abstract: Both human parvovirus B19 (B19V) and human bocavirus (HBoV) are known to be important human pathogens of the Parvoviridae family. Our earlier investigation demonstrated that both B19V-VP1u and HBoV-VP1u have a significantly disruptive effect on tight junctions (TJs) in A549 cells, implying the essential role of parvovirus in airway infection and lung injury. However, no direct evidence that B19V-VP1u and HBoV-VP1u induce lung injury exists. The present study further investigates the induction of lung injury by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The investigators speculate that specific viral agents causing CAP may induce the production of interleukin-6, and lead to thrombocytosis. The increased release of interleukin-6 was reported during parainfluenza virus and human bocavirus infection in vitro and mice experiments [22,23]. Interleukin-6 induces and increases expression of hepatic thrombopoietin mRNA and consequential thrombocytosis.…”
Section: Discussionmentioning
confidence: 87%
“…The investigators speculate that specific viral agents causing CAP may induce the production of interleukin-6, and lead to thrombocytosis. The increased release of interleukin-6 was reported during parainfluenza virus and human bocavirus infection in vitro and mice experiments [22,23]. Interleukin-6 induces and increases expression of hepatic thrombopoietin mRNA and consequential thrombocytosis.…”
Section: Discussionmentioning
confidence: 87%
“…Human parvovirus B19 (B19V) and human bocavirus (HBoV) are important pathogenic parvoviruses that have been associated with a variety of human disorders [24]. Many global reports have indicated that there are associations between respiratory diseases and HBoV or B19V [1014, 25–26]. However, the influence of B19V-VP1u and HBoV-VP1u on the development of asthmatic symptoms is still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, an alternative method that can mimic the symptoms induced by human parvovirus infection was sought. Accordingly, various studies have indicated that the subcutaneous injection of recombinant B19V-VP1u proteins into mice induces myocardial injury, dilated cardiomyopathy and lung injury, which are recognized as a model for the systemic effects of parvovirus infection [14, 29]. Notably, a study of a dilated cardiomyopathy mouse model that is generated with the subcutaneous injection of B19V-VP1u reported that siderophages, known as heart failure cells, were observed in lung tissues [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations